2016
DOI: 10.2169/internalmedicine.55.6896
|View full text |Cite
|
Sign up to set email alerts
|

Severe Disseminated <i>Mycobacterium avium</i> Infection in a Patient with a Positive Serum Autoantibody to Interferon-γ

Abstract: We herein report a case of disseminated Mycobacterium avium infection that involved both optic nerves, the conjunctiva, the right lower lung, and multiple skin lesions, including a thoracic nodule. The patient was a 65-year-old man without any significant medical history. The pathogen was detected in the patient's eye discharge, sputum, bronchial lavage fluid, and thoracic nodule. Anti-mycobacterial chemotherapy, including clarithromycin, rifampicin, and ethambutol, was administered, and the thoracic nodule wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Some interesting reports with more unusual presentations of nAIGA-related infection were recently published. Ikeda et al [12] reported a 65-year-old man from Japan with disseminated Mycobacterium avium infection involving both optic nerves in the context of wide dissemination. The neutralizing capacity of the AIGA was confirmed by STAT1 phosphorylation testing and as well reflected by an ‘invalid’ quantiferon assay showing no IFN-γ response to phytohemagglutinine [12].…”
Section: Autoantibodies To Ifn-γ Cause Susceptibility To Opportunistimentioning
confidence: 99%
See 3 more Smart Citations
“…Some interesting reports with more unusual presentations of nAIGA-related infection were recently published. Ikeda et al [12] reported a 65-year-old man from Japan with disseminated Mycobacterium avium infection involving both optic nerves in the context of wide dissemination. The neutralizing capacity of the AIGA was confirmed by STAT1 phosphorylation testing and as well reflected by an ‘invalid’ quantiferon assay showing no IFN-γ response to phytohemagglutinine [12].…”
Section: Autoantibodies To Ifn-γ Cause Susceptibility To Opportunistimentioning
confidence: 99%
“…Ikeda et al [12] reported a 65-year-old man from Japan with disseminated Mycobacterium avium infection involving both optic nerves in the context of wide dissemination. The neutralizing capacity of the AIGA was confirmed by STAT1 phosphorylation testing and as well reflected by an ‘invalid’ quantiferon assay showing no IFN-γ response to phytohemagglutinine [12]. Koizumi et al [13] presented a case of a 66-year-old Japanese HIV negative man with M. avium peritonitis and chylous ascites and nAIGA.…”
Section: Autoantibodies To Ifn-γ Cause Susceptibility To Opportunistimentioning
confidence: 99%
See 2 more Smart Citations
“…The most common assay used to detect anti-IFN-c AAbs is the enzyme-linked immunosorbent assay (ELISA), in indirect, 2,12,17,18,21,23,[36][37][38][39][40][41] sandwich, 14,16,32,42 or inhibitory 2,3,8,17,23,32,37,43,44 assay format. For the ELISAbased method, the results could be reported qualitatively (positive or negative) or quantitatively as optical density (OD), 39 titer, 43 or through calculations of arbitrary units 21 or ELISA units (EU). 36,39 The easy-to-use, low-cost Dot ELISA strip, which can be read directly on the strip, was developed as a point-of-care screening tool in remote settings.…”
Section: Detection Of Anti-ifn-c Aabsmentioning
confidence: 99%